Selection Criteria in C.B.P. - Chifflet, Juan; Bogliaccini, Gustavo; Bertullo, Hugo; Domínguez, Carlos (Cirugía del Uruguay, 1982)
Extension, histological type and host condition are the most important factors influencing prognosis in lung cancer. The best results are given by surgery which must be selective, otherwise it may become harmful. The most important repercussions of resective approach are in the respiratory and cardiovascular system. According to lung and cardiovascular function, patients are divided in 3 groups: poor and high risk patients and the inoperable ones. TNM classification approved in 1978 in Argentina is used when evaluating lung cancer spread. The histotogical classification chosen is that one which divides tumors in oat-cell and not oat-cell. The oat-cel carcinoma, those in stage IV are inoperable. Patients in stage I and II are surgical candidates. Those in stage III are difficult to manage. Surgery in this stage must be performed when there are maximum possibilities of complete resection. Node involvement leads us to a worse prognosis mainly if it is a mediastinal involvement.